Seasonal Variations of Volcanic Ash and Aerosol Emissions around Sakurajima Detected by Two Lidars - Atsushi Shimizu; Masato Iguchi; Haruhisa Nakamichi (Atmosphere, 2021)
Two polarization-sensitive lidars were operated continuously to monitor the three-dimensional distribution of small volcanic ash particles around Sakurajima volcano, Kagoshima, Japan. Here, we estimated monthly averaged extinction coefficients of particles between the lidar equipment and the vent and compared our results with monthly records of volcanic activity reported by the Japan Meteorological Agency, namely the numbers of eruptions and explosions, the density of ash fall, and the number of days on which ash fall was observed at the Kagoshima observatory. Elevated extinction coefficients were observed when the surface wind direction was toward the lidar. Peaks in extinction coefficient did not always coincide with peaks in ash fall density, and these differences likely indicate differences in particle size.